2011
DOI: 10.1007/s11426-011-4251-9
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation of olefins with hydrogen peroxide catalyzed by a reusable lacunary-type phosphotungstate catalyst

Abstract: Olefins and allylic alcohols have been epoxidized with commercially available hydrogen peroxide (30% H 2 O 2 ) using a phase transfer catalyst, composed of cetyltrimethylammonium cations and a lacunary-type phosphotungstate anion [PW 11 O 39 ] 7 or the complete Keggin-type heteropolyanion [PW 12 O 40 ] 3 , under two-phase conditions using ethyl acetate as the solvent. It was found that the lacunary-type catalyst showed higher activity and better recyclability than the complete Keggin-type catalyst under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In our previous work, we have demonstrated that lacunary-type phosphotungstate could be degraded to {PO 4 [WO(O 2 ) 2 ] 4 } 3À by aqueous hydrogen peroxide in the epoxidation reaction and could recover the original structure after the reaction in the presence of excess substrate. 26 In this work, the degraded species might be stabilized by the functionalized cation in the presence of a slight excess of H 2 O 2 .…”
Section: Catalytic Performancesmentioning
confidence: 94%
See 1 more Smart Citation
“…In our previous work, we have demonstrated that lacunary-type phosphotungstate could be degraded to {PO 4 [WO(O 2 ) 2 ] 4 } 3À by aqueous hydrogen peroxide in the epoxidation reaction and could recover the original structure after the reaction in the presence of excess substrate. 26 In this work, the degraded species might be stabilized by the functionalized cation in the presence of a slight excess of H 2 O 2 .…”
Section: Catalytic Performancesmentioning
confidence: 94%
“…The lacunary-type phosphotungstate anion [PW 11 O 39 ] 7À was proved to be an efficient catalyst precursor for the epoxidation of olefins in our previous work. 26 Herein, the coupling of [PW 11 O 39 ] 7À anion with PEG-functionalized ammonium cation resulted in a functionalized IL (PEG-PW 11 ), which was shown to have excellent catalytic activity in the epoxidation reaction even at a molar ratio of the substrate to catalyst of nearly 500 : 1 (Fig. 3).…”
Section: Catalytic Performancesmentioning
confidence: 99%
“…Indeed, in the 350 °C-450 °C range, the HPMo is gradually transformed but it still exists. Like all heteropolyanions, HPMo is a superacid with a very strong oxidizing power [40,41]. So the presence of HPMo leads to further oxidation, i.e.…”
Section: Effect Of Calcination Temperaturementioning
confidence: 99%
“…The reusability of the catalyst could be realized by decreasing the temperature after the reaction, making the recovery of the catalyst easier. Hua et al studied a reusable phosphotungstate catalyst composed of cetyltrimethylammonium cations and [PW 11 O 39 ] 7– ; 51.8% H 2 O 2 conversion and 73% product selectivity could be achieved, and they found that benzaldehyde was the main byproduct. Similarly, Zhao et al developed a phase-transfer catalyst for the epoxidation of olefins.…”
Section: Introductionmentioning
confidence: 99%